The Impact of a Community-University Partnership Program on Special Education Teacher Training in Autism Spectrum Disorder - Shamash, Emily R.; Martin, Alyson M. (Journal of the American Academy of Special Education Professionals, 2021)
The need for highly qualified teachers who have experience and training with students with ASD continues to grow. In order to meet the need for high quality supervised field experiences for teacher candidates as well as opportunities for students with ASD to gain exposure to post-secondary activities on a University campus, the Transition Opportunities for Post-Secondary Success (TOPS) program was launched. This program offered a unique opportunity for both undergraduate and graduate pre-service regular and special educators to gain hands-on practical experience teaching students with ASD under the guidance of highly qualified special educators. Assisting in the TOPS program offered practical experiences that mirrored theoretical and practical approaches taught in the higher education classroom. Survey data was collected on the TOPS assistant experiences with regard to the impact on their future professional interest in special education and ASD and the overall perceived value of the training. A synthesis of results and next steps for research and practice are discussed.